2013
DOI: 10.1158/1541-7786.mcr-12-0095
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of HIF-1α in 4E-BP1 Gene Expression

Abstract: The eukaryotic translation initiation factor 4E (eIF4E) is necessary for the translation of capped mRNAs into proteins. Cap-dependent mRNA translation can be however inhibited by the eIF4E-binding protein 1 (4E-BP1). The hypophosphorylated forms of 4E-BP1 indeed sequester eIF4E and thus block translation initiation and consequent protein synthesis. Different reports indicate that, in addition to hypophosphorylation, 4E-BP1 function can be also regulated at the level of protein expression. This is the case in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…The constant 1:1 ratio for EIF4G1:EIF4A1 and 8:1 for EIF4G1:EIF4E in healthy tissues confirm a previous report that transcription of EIF4F subunits for CDTI is highly coordinated (Lin et al, 2008). Furthermore, the EIF4E promoter contains hypoxia-responsive elements (HREs) that can be directly regulated by HIF1α under hypoxic conditions (Azar et al, 2013;Yi et al, 2013). Since HREs overlap the E-box motifs in EIF4E promoter, c-Myc and HIF1α compete for the transcription regulation of EIF4E (Gordan et al, 2007), which may perturb the coordinated transcription between EIF4G1 and EIF4E.…”
Section: Computational Analyses Of Eif4f Expression Conform To Biochesupporting
confidence: 88%
“…The constant 1:1 ratio for EIF4G1:EIF4A1 and 8:1 for EIF4G1:EIF4E in healthy tissues confirm a previous report that transcription of EIF4F subunits for CDTI is highly coordinated (Lin et al, 2008). Furthermore, the EIF4E promoter contains hypoxia-responsive elements (HREs) that can be directly regulated by HIF1α under hypoxic conditions (Azar et al, 2013;Yi et al, 2013). Since HREs overlap the E-box motifs in EIF4E promoter, c-Myc and HIF1α compete for the transcription regulation of EIF4E (Gordan et al, 2007), which may perturb the coordinated transcription between EIF4G1 and EIF4E.…”
Section: Computational Analyses Of Eif4f Expression Conform To Biochesupporting
confidence: 88%
“…They also showed that the loss of Smad4, an oncogenic driver in human pancreatic cancer, results in the loss of 4E-BP1 expression and promotes prooncogenic unopposed eIF4E activity, which can be blocked by enforced reexpression of 4E-BP1 (80,81). Intriguingly, HIF1␣ was found to coassociate Smad3/4 and to increase the level of hypoxia-dependent transcription of 4E-BP1, thereby implicating the loss of Smad4 in the failure of pancreatic cancer cells to inhibit protein synthesis during hypoxia (82). Other studies whose findings are consistent with those of our work include those that have observed that overexpression of eIF4E, in concert with certain TGF-␤ pathway single nucleotide polymorphisms in colon cancer cells, is associated with increased TGF-␤ stimulation of adhesion molecule expression (83).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, contrary to the expected outcome of increased PI3K signaling resulting in equivalent eIF4E activation across all cell prostate epithelial types, our data uncovered cell-type specificity in 4EBP1 transcript abundance that primes cells for drug sensitivity or resistance. In the future, it will be interesting to determine the molecular basis for the increased 4EBP1 expression in luminal epithelial cells compared to basal epithelial cells and whether these differences arise from transcription factor promoter binding (26, 27), chromatin remodeling, or mRNA degradation rates.…”
Section: Discussionmentioning
confidence: 99%